2004
DOI: 10.1364/opex.12.004189
|View full text |Cite
|
Sign up to set email alerts
|

Optical parametric master oscillator and power amplifier for efficient conversion of high-energy pulses with high beam quality

Abstract: Abstract:We describe a system for parametric conversion of high-energy, Q-switched laser pulses from 1.064 µm to 2.1 µm in KTiOPO 4 . High beam quality and efficiency are obtained by use of a two-stage system: An optical parametric oscillator (OPO) pumped by a narrow beam with 8 mJ of energy, generates 1.9 mJ of signal energy for seeding an optical parametric amplifier (OPA). With 500 mJ pump energy, different OPA configurations produce up to 138 mJ signal energy with M 2 ≈ 2.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 12 publications
2
51
1
Order By: Relevance
“…According to the work of Arisholm et al, 12 this can improve beam quality and output power. The KTP crystals are cut in a critical phase-matching configuration (θ ¼ 76 deg, ϕ ¼ 0 deg).…”
Section: Frequency Conversion Unitmentioning
confidence: 98%
“…According to the work of Arisholm et al, 12 this can improve beam quality and output power. The KTP crystals are cut in a critical phase-matching configuration (θ ¼ 76 deg, ϕ ¼ 0 deg).…”
Section: Frequency Conversion Unitmentioning
confidence: 98%
“…To maintain the beam quality at the output the KTP crystals are oriented in a walk-off compensation configuration. A dichroic mirror is inserted between the second and the third crystal to mitigate back-conversion defects, following the approach from [7].…”
Section: Laser Transmittermentioning
confidence: 99%
“…To maintain a high beam quality at the output, the four bulk 20 mm long KTP amplifiers are oriented in a walk-off compensation configuration, and a filtering mirror, highly reflective for the idler wave, is inserted between crystal 2 and crystal 3 in order to mitigate back-conversion defects. Indeed, it has already been shown that such idler suppression scheme reduces saturation and thus limits its detrimental effects such as beam quality deterioration [5]. The performances of the source are measured at 2.05 µm, in the vicinity of the R30 CO 2 line.…”
Section: µM Transmitter Benchmentioning
confidence: 99%